Riwayat Keluarga, Aktivitas Fisik dan Pola Makan terhadap Kejadian Dismenorea Primer pada Wanita - Tasya Septiyani; Sarmalina Simamora (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2021)
Primary dysmenorrhea is menstrual pain since menarche, there are no abnormalities in the uterus. Family history is a risk factor for primary dysmenorrhea. Physical activity and a good diet of women have the possibility to prevent it happening. This study aims to analyze the relationship between family history, physical activity and diet with the incidence of primary dysmenorrhea in women. This research is an analytic observational study with a cross-sectional approach. Sampling was done by the accidental non-probability sampling method. Data collection was taken based on respondents' answers to online questionnaires. The measuring tool used is the google form. 58.0% of respondents had a family history of primary dysmenorrhea, 91.6% of respondents did not have sufficient physical activity and 95.5% did not have a good diet. The results of the Chi-square test showed that family history had a significant relationship with the incidence of primary dysmenorrhea with a p-value of 0.000 < 0.05. Physical activity and diet did not have a relationship with the incidence of primary dysmenorrhea (p-value 0.285 and p-value 0.419). Generally, respondents in this study have a poor diet and physical activity, so this affects the results of the analysis. To get a more adequate answer, it is necessary to conduct research with a good diet and physical activity intervention design for dysmenorrhea respondents.